Rare Copy Number Variations in a Chinese Cohort of Autism Spectrum Disorder - Fan, Yanjie; Du, Xiujuan; Liu, Xin; Wang, Lili; Li, Fei; Yu, Yongguo (Frontiers in Genetics, 2018)
Autism spectrum disorder (ASD) is heterogeneous in symptom and etiology. Rare copy number variations (CNVs) are important genetic factors contributing to ASD. Currently chromosomal microarray (CMA) detecting CNVs is recommended as a first-tier diagnostic assay, largely based on research in North America and Europe. The feature of rare CNVs has not been well characterized in ASD cohort from non-European ancestry. In this study, high resolution CMA was utilized to investigate rare CNVs in a Chinese cohort of ASD (n=401, including 177 mildly/moderately and 224 severely affected individuals), together with an ancestry-matched control cohort (n=197). Diagnostic yield was about 4.2%, with 17 clinically significant CNVs identified in ASD individuals, of which 12 CNVs overlapped with recurrent autism risk loci or genes. Autosomal rare CNV burden analysis showed an overrepresentation of rare loss events in ASD cohort, whereas the rate of rare gain events correlated with the phenotypic severity. Further analysis showed rare losses disrupting genes highly intolerant of loss-of-function variants were enriched in ASD cohort. Among these highly constrained genes disrupted by rare losses, RIMS2 is a promising candidate contributing to ASD risk. This pilot study evaluated clinical utility of CMA and the feature of rare CNVs in Chinese ASD, with candidate genes identified as potential ASD risk factors.